The Construction of A 'New' Man in Disney's Frozen II (2019) - Paramitha, Annisa Maudy (2020)
Masculinity is categorized into several types and in literature, it is constructed through many means. Much has been said about masculinity construction in literature, but little examines it in children's literature, more specifically children's films -which arguably conveys its marginality in the study of literature. This study emphasizes on the construction of a new idea of male gender by showcasing Disney's Frozen II (2019)'s main male character named Kristoff. Using Connell's (2005) theory of masculinity, Heintz and Stracey's (2006) film theory and Boggs & Petrie's (2008) characterization in films, this research is a textual analysis in nature. The finding reveals that masculinity in Frozen II (2019) is constructed through characterization and cinematic aspects. This study proves that Kristoff's characterization is fluid, shifting between two masculinities which are hegemonic masculinity and complicit or 'new' masculinity. Moreover, through cinematic aspects such as mise-en-scène and song lyrics, Disney constructs Kristoff as a 'new' man who is more sensitive than the typical hegemonic masculinity. Thus, the implication of this research to the studies of children's literature is to make the readers aware that there are many variations of masculinities and there is a shift in the gender-stereotypical heroes and heroines in Disney's film.